Penerapan Target Costing sebagai Upaya Menurunkan Harga Pokok Produksi untuk Mempertahankan Sustainability Perusahaan PT Indika Energy Tbk. - Pendi Simarmata (Sekolah Pascasarjana Perbanas Jakarta, 2022)
The purpose of this research is to study how target costing implementation Target Costing on cost of good Sold Reduction for Company Sustainability: “PT. Indika Energy Tbk” tapay, in order to reach the desired sustainability. The difficulties on managing cost and getting desired sustainainability in “PT.Indika Energy Tbk” tapay was the reason and motivation behind this research. To get all the data that needed in this research, researcher choose to do observation the production manager and the owner of “PT. Indika Energy. The production cost calculated the company and the alternative production cost calculated by researcher, were analyzed and compared each other to know how good the target costing implementation. The result of this research shows that target costing implementation in “PT. Indika Energy” tapay was good and fit. Implementation of target costing can raise the sustainability of Company as much as the desired profit. And then, the company can manage the production cost on its product. Keywords: production cost, profit target, target costing, selling price